Overcoming dormancy in Bauhinia scandens seeds - Jeromini, Tatiane Sanches [UNESP]; Pereira, Thaís Soares; Martins, Cibele Chalita [UNESP]; Da Silva, Givanildo Zildo (Universidade Estadual de Londrina, 2020)
Bauhinia scandens, an ornamental climbing vine, recently introduced in Brazil, in 2006 which has been gaining prominence due to its anti-tumor medicinal properties. A common feature amongst species of the Fabaceae family is dormancy due to the impermeability of the integument of the seed to water. The demand for seedlings of this species makes it necessary to elucidate the germination process and initial seedling growth. The objective of this study was to determine a method to overcome dormancy, thereby promoting seed germination and initial growth of B. scandens seedlings. The seeds were subjected to one of four treatments, besides the control: mechanical scarification, immersion in water (26 °C for 24 hours), immersion in hot water (86 °C for 24 hours, then 26 °C) and immersion in H2SO4 (95%) for 15, 30, 45, and 60 minutes. The seeds were evaluated for water content, germination (normal, abnormal seedlings, dormant and dead seeds), first count, mean germination time and relative frequency of germination. The seedlings were evaluated for emergence in sand, first count, emergence speed index, length and dry matter mass. B. scandens seeds should be immersed in H2SO4 for 45 and 60 minutes before sowing to overcome dormancy, in order to promote and standardize seed germination and enhance initial growth of the seedlings.
Keywords: Antitumor properties; Bauhinia-climbing vine; Fabaceae; Relative frequency